Q: What is -6x - x 10 15 -7x - 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(7x-3)(2x+5) 14x2 + 29x - 15, write 29x = 35x - 6x = 14x2 - 6x + 35x - 15 = (14x2 - 6x) + (35x - 15) = 2x(7x - 3) + 5(7x - 3) = (7x-3)(2x+5)

Given 6x + (7x-8) = -5 6x + 7x - 8 = -5 ==> 13x = 3 therefore, x = 3/13

(7x - 1)(6x + 5)

Example: 7x + 10 - {2(x + 3) - 3(x - 2) + 5} = 7x + 10 - {2x + 6 - 3x + 6 + 5} = 7x + 10 - {2x - 3x + 6 + 6 + 5} = 7x + 10 - {x + 17} = 7x + 10 - x - 17 = 7x - x + 10 - 17 = 6x - 7

6x - 12 + 4x + 5 = 06x + 4x = 12 - 510x = 7x = 7/10

Related questions

(7x-3)(2x+5) 14x2 + 29x - 15, write 29x = 35x - 6x = 14x2 - 6x + 35x - 15 = (14x2 - 6x) + (35x - 15) = 2x(7x - 3) + 5(7x - 3) = (7x-3)(2x+5)

Given 6x + (7x-8) = -5 6x + 7x - 8 = -5 ==> 13x = 3 therefore, x = 3/13

(7x - 1)(6x + 5)

Example: 7x + 10 - {2(x + 3) - 3(x - 2) + 5} = 7x + 10 - {2x + 6 - 3x + 6 + 5} = 7x + 10 - {2x - 3x + 6 + 6 + 5} = 7x + 10 - {x + 17} = 7x + 10 - x - 17 = 7x - x + 10 - 17 = 6x - 7

6x - 12 + 4x + 5 = 06x + 4x = 12 - 510x = 7x = 7/10

-8 + 7(6x) + 3 = -7x - 5 - 1-8 + 42x + 3 = -7x - 5 - 142x - 8 + 3 = -7x - 5 + (-1)42x - 5 = - 7x - 642x + 7x - 5 + 5 = - 7x + 7x - 6 + 549x = -149x/49 = -1/49x = -1/49

14x2 + 29x - 15= 14x2 + 35x - 6x - 15= 7x(2x + 5) - 3(2x + 5)= (2x + 5)(7x - 3)

6x - 5 -5 = 0 6x -10 = 0 +10=+10 6x=10 x= about 1.4

X=2

6x - 5y = 15 6x - 6x - 5y = 15 - 6x -5y = -6x + 15 (-5y)/-5 = (-6x)/-5 + 15/-5 y = 6/5x - 3 where 6/5 is the slope and y-intercept is -3.

7x+20-15=7x+5

-3*6x+5/8=6x-1 * (-3*(6x+5))/8?If this is your question, then:LHS = -3 * 6x + 5/8 = -18x + 5/8RHS = 6x - 1 * (-18x-15)/8 = 6x + (18x+15)/8 = 48x/8 + 18x/8 + 15/8 = 66x/8 + 15/8-18x + 5/8 = 66x/8 + 15/866x/8 + 18x = 15/8 - 5/8210x/8 = 10/8210x = 10x = 10/210 = 1/21